2006
DOI: 10.1155/jbb/2006/51516
|View full text |Cite
|
Sign up to set email alerts
|

Nanomedicine: Techniques, Potentials, and Ethical Implications

Abstract: Nanotechnology is concerned with materials and systems whose structures and components exhibit novel physical, chemical, and biological properties due to their nanoscale size. This paper focuses on what is known as nanomedicine, referring to the application of nanotechnology to medicine. We consider the use and potentials of emerging nanoscience techniques in medicine such as nanosurgery, tissue engineering, and targeted drug delivery, and we discuss the ethical questions that these techniques raise. The ethic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
57
0
5

Year Published

2008
2008
2017
2017

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(65 citation statements)
references
References 48 publications
0
57
0
5
Order By: Relevance
“…While it has been suggested that nanomedical ethics as a field has not received much attention [15] it certainly cannot be alleged that the topic has not been charted analytically (e.g. [3][4][5][16][17][18]). In addition to these mainly theoretical discussions of potential ethical issues, the general public perception has been mapped through public consultations (e. g. [19] who study and monitor the environmental materials that are created by the 'upstream' scientists [7].…”
Section: Discussionmentioning
confidence: 99%
“…While it has been suggested that nanomedical ethics as a field has not received much attention [15] it certainly cannot be alleged that the topic has not been charted analytically (e.g. [3][4][5][16][17][18]). In addition to these mainly theoretical discussions of potential ethical issues, the general public perception has been mapped through public consultations (e. g. [19] who study and monitor the environmental materials that are created by the 'upstream' scientists [7].…”
Section: Discussionmentioning
confidence: 99%
“…Currently, the ethical considerations involved in nanomedicine are related to risk assessment in general, somatic-cell versus germline-cell therapy, the enhancement of human capabilities, risk management of engineered nanomaterials, research into human embryonic stem cells and the toxicity of nanoparticles and nanomedicine, uncontrolled function and self-assembly of nanoparticles [12,17]. For instance, recently, the identification of cytotoxicity of nanoparticles toward mammalian gremline stems cells has aroused great concern over the biosafety of nanomaterials [18].…”
Section: Ethical Issues In Nanomedicinementioning
confidence: 99%
“…Initially, the dsRNAs are cleaved into siRNAs by a ribonuclease known as a 1 Introduction Dicer. [40] The siRNA is double-stranded, and the length usually varies between [21][22][23] nucleotides. The siRNAs gets incorporated into ribonuleotide protein components called RNA-induced silencing complex (RISC) and by unwinding the duplex, triggered through Argonaute 2, the catalytic core within RISC, the complex becomes activated RISCs.…”
Section: Rna Interferencementioning
confidence: 99%
“…Since gene therapy in germline cells affect not only the individual cells that develop from it, but also their offspring and successive generations, gene therapy on germline cells is forbidden. [22][23] The successful application of gene therapy is still a great challenge in ongoing research, since the most difficult obstacles to overcome have been the inability to transfer the 1 Introduction appropriate gene to a target, prolonged gene expression, and to obtain low toxicity. [24][25] Gene transfer of a nucleic acid to somatic cells can take place either in vivo or ex vivo and the process by which genes are transferred into cultured mammalian cells is called transfection.…”
Section: Introductionmentioning
confidence: 99%